ANALISIS BEBAN KERJA MENGGUNAKAN METODE FULL TIME EQUIVALENT (FTE) UNTUK MENGOPTIMALKAN TENAGA KERJA DI GROUP PENGADAAN PT XYZ - Nurfajriah; Salsa Febriyanti; Siti Nasution (Journal of Optimization System and Ergonomy Implementation, 2024)
PT XYZ is a company based in logistics services, handling, and port development that recently merged to improve the quality of the company. So there have been many changes, and one of those affected is the head office procurement group. The impact that occurred in the head office procurement group was the formation of the SSC (Shared Service Center) organization. The formation of the SSC resulted in the reassignment of several employees in the procurement group. Therefore, to find out the workload experienced by using Full Time Equivalent (FTE) calculations, this research was undertaken. Based on the calculation of workload with Full Time Equivalent (FTE), The workload experienced is included in the underloaded workload category for all employees because it is in the range 0–0.99. Where the number of permanent employees is 10 and does not experience changes due to workload. Therefore, to overcome the overloaded workload, it is possible to make adjustments to the distribution of work procedures between positions evenly, map the work process by adjusting the balanced specifications and qualifications of employees against the latest organizational structure, and carry out a comparative analysis of psychological workload.